GE_GERICHTE P/10770/2018 vom 8. März 2019 - GE Cour de justice (2019)
OPPOSITION(PROCÉDURE) ; NOTIFICATION IRRÉGULIÈRE ; DOMICILE À L'ÉTRANGER ; DOMICILE CONNU ; ASSISTANCE JUDICIAIRE | CPP.356; CPP.87; CPP.88; CPP.135